Determinants That Influence Adoption of Mobile Technology In Learning Environment - Manimekalai, Jambulingam (2014)
This research aims to investigate the salient factors that influence the behavioural intention on adoption of mobile technology in the learning environment. Rapid growth of Third Generation (3G) mobile technology has changed our student’s life style radically. It incorporates voice data and internet access, which turns the smart phone equal to a computer system. This ubiquities feature extends opportunities into learning environment. This study is to find out the determinants that influence the adoption of mobile technology among the undergraduate students and to increase learning activities using mobile technologies in the universities in future. The modified Unified Theory of Acceptance and Use of Technology (UTAUT) model adopted to determine the factors that influence the behavioural intention to use mobile technology in the learning environment. Structural Equation Modeling technique (SEM) employed for analysing the data collected from 351 students. The result indicates that Performance Expectancy, Affordability and Podcast are the salient factors that influence the behavioural intention on adopting mobile technology in learning environment and age and gender do not have a significant effect on adopting mobile technology. The study contributes to the body of knowledge in the area of adoption of mobile technology and provides a foundation for future implementation of mobile learning in educational institutions.